PENGARUH GAYA KEPEMIMPINAN, TUNJANGAN, LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT. CRESTEC INDONESIA - PASURUAN - Khumairoh, Nur Sitti; EDS, Efi; Mastoanah, Lilik (Nusantara Hasana Journal, 2022)
The purpose of this study is to find out the impact of Leadership Style, Benefits, and Physical Work Environment on Employee Performance. This research uses quantitative approach methods with a population are employees of the production section at PT. CRESTEC INDONESIA - PASURUAN as many as 158 employees, using the formula Slovin obtained a total of 62 respondents, and sampling techniques using simple random sampling and analysis techniques used is multiple linear analysis. The results of this study showed that partially (test t) there is a positive and significant influence between leadership style on performance. Partially (test t) the benefit has a positive and significant effect on Performance. Partially (test t) The Physical Work Environment has a positive and significant effect on Performance and Leadership Style, Benefits, and Physical Work Environment simultaneously (test F) positively and significantly on Performance.